Urban Form and Real Estate Value in Msheireb Downtown Doha, Qatar - Aliyar, Adheena Kottappurath; Major, Mark David; Tannous, Heba O; Al-Esmail, Fatima R A (Alanya Üniversitesi, 2023)
In the late 20th century, Doha’s rapid urbanization and globalization led to the loss of housing and the compact, traditional urban fabric in the old city center. The Qatari government and Msheireb Properties developed Msheireb Downtown Doha to bring urban living back with a contemporary re-interpretation of the traditional urban fabric and modern life conveniences. Our study's primary objective is to investigate the relationship between urban form and the rental value of residential units, identifying factors that might influence rental asking prices. The paper examines morphological characteristics through field surveys and the real-estate variables such as location, floor area, number of bedrooms/bathrooms, and asking price collected from publicly available real estate websites. The findings indicate that the residential units' layout and adjacent streets' morphological characteristics clearly define specific targeted user groups. Larger residential units target Qatari families via more bedrooms/bathrooms and quieter urban settings, emphasizing Islamic cultural values. Smaller units target ex-pat workers (especially Westerners) using open-plan layouts in more lively urban environments of the development. The price per square meter also increases for residential units closer to the Doha Metro station. The study reiterates the success of compact living for improving urban living in other neighborhoods of old Doha.